2020
DOI: 10.1101/2020.04.14.041624
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The evolution of sex-biased gene expression in theDrosophilabrain

Abstract: Genes with sex-biased expression in Drosophila are thought to underlie sexually dimorphic phenotypes and have been shown to possess important evolutionary properties. However, the forces and constraints governing the evolution of sex-biased genes in the somatic tissues of Drosophila are largely unknown. Using population-scale RNA sequencing data we show that sex-biased genes in the Drosophila brain are highly enriched on the X Chromosome and that most are biased in a species-specific manner. We show that X-lin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…3A, Table 1). While the study of protein evolution of sex-biased brain genes (brains sensu stricto , rather than simply heads, or pooled brain-eye tissues as considered by some previous studies (Catalan et al, 2018, Congrains et al, 2018)) remains rare, rapid evolution of female-biased brain genes has been reported in some bird embryos (Mank et al, 2007), and in some autosomal genes in flies (Khodursky et al, 2020). However, an opposite pattern of rapid evolution of male-biased brain genes for several stages of development was reported in humans (Shi et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3A, Table 1). While the study of protein evolution of sex-biased brain genes (brains sensu stricto , rather than simply heads, or pooled brain-eye tissues as considered by some previous studies (Catalan et al, 2018, Congrains et al, 2018)) remains rare, rapid evolution of female-biased brain genes has been reported in some bird embryos (Mank et al, 2007), and in some autosomal genes in flies (Khodursky et al, 2020). However, an opposite pattern of rapid evolution of male-biased brain genes for several stages of development was reported in humans (Shi et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The brain is a major tissue type providing the neurological basis for the mating behaviors of courtship, intrasex competition, mate-choice, and post-mating male-female responses (Wright & Mank, 2013, Mank et al, 2007, Dalton et al, 2010, Naurin et al, 2011). Male and female differences in gene expression per se in the brain have been examined in some insects and vertebrates (Mank et al, 2007, Small et al, 2009, Santos et al, 2008, Naurin et al, 2011, Catalan et al, 2012, Shi et al, 2016, Tomchaney et al, 2014, Ingleby et al, 2014, Wright & Mank, 2013, Yang et al, 2016, Jagadeeshan & Singh, 2005, Khodursky et al, 2020, Huylmans & Parsch, 2015). Further, in Drosophila , analyses of a small number of neural genes are directly connected to mating functions and behaviors (Drapeau et al, 2003, Kadener et al, 2006, Dauwalder, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reflecting the notion that directional selection should both increase divergence between groups and decrease variation in the group under selection, delta-x takes higher values the higher divergence and the lower polymorphism. Low expression polymorphism relative to interspecific divergence is a hallmark of adaptive evolution (Nuzhdin et al 2004;Ometto et al 2011;Khodursky et al 2020).…”
Section: Evolution Of Sbge Across the Genus Leucadendronmentioning
confidence: 99%